Recovery of ro-pax ferry traffic from Covid-19 under tightening environmental regulations: Case Helsinki-Tallinn - Ulla Tapaninen; Riina Palu (Journal of Shipping and Trade (JST), 2022)
In 2020, the number of passengers on international ro-pax ferries collapsed due to the pandemic caused by the Covid-19 virus and subsequent travel restrictions. At the same time, both the International Maritime Organisation and the European Union are setting stringent regulations on carbon dioxide emissions from ships. In this research, we look at what options companies offering ro-pax services have to recover from the Covid-19 pandemic under-tightening environmental regulations and the future options for the industry. The case under study is ro-pax ferry traffic between Helsinki and Tallinn. It is one of the busiest international passenger ferry connections in the world. The economics of transport are based on large high-speed vessels, the combination of passengers and cargo, and sales onboard. We created four scenarios for the traffic: to continue the same high-speed ro-pax system as in 2019, to reduce the number of vessels, to switch to new types of ships, to slow down the speed of the vessels or to divide traffic into faster and slower ships. The research contributes to discussion of competitive strengths of ro-pax transport.
Keywords: 650; Covid-19; Decarbonisation; Helsinki-Tallinn; Ro-Pax traffic; Ro-ro traffic